Proclamation of Charles Manley Smith - Smith, Charles Manley, 1868-1937.
Proclamation by Governor Smith designating December 26 as Ethan Allen Day in the State of Vermont.
Governor of Vermont.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Allen, Ethan, -- 1738-1789 -- Anniversaries, etc; Holidays -- Vermont; Governors -- Vermont